PERILAKU PEMUKIM TERHADAP LAHAN PERMUKIMAN SEKITAR SUNGAI DI KAWASAN PUSAT KOTA - Najib, Muhammad (MEKTEK, 2005)
The aim of this research for knowed residents behavior pattern in to land use settlements camprises behariors and land use spatial variation on riverside settlement at downtown section. The result of this research show that the settlements land use by residents as maximal (has an intensive) for residential activity, working and social interaction executed. The openspaces are forms dominant space at used until to become orientation and activity residents center. Because the land so lack that increasing houses spaces also on the result spaces at houses site without considerating to safety factor, healthy and settlement neighborhood condition with suitable to settle. Construct the public fasilities neighborhood with result space used on the main roads or the common spaces because the fasilities also using together or group